2019
DOI: 10.3390/ani9030101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Environment Enrichments on Behaviour and Social Interactions in Growing Pigs

Abstract: (1) Background: Pigs are active animals that require a suitable environment to be able to express their exploratory behaviour. The aim of the present study was to compare the effects of different environmental enrichments on the behaviour, social interactions, salivary cortisol concentration and body weight of pigs during the growing phase. (2) Methods: The investigation involved 75 pigs divided into three groups. The environmental enrichments were arranged as follows: Hanging metal chains for the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These objects do not meet the needs of pigs (as defined above) and can pose a hazard as they are unsafe (e.g., ingestible metal parts in car tyres [35]). Many studies have confirmed that objects such as chains, plastic pipes and balls or car tyres should not be recommended for long-term use, as they are not effective enrichment (e.g., [87,88]), do not meet the criteria of effectiveness and can quickly lose their novelty factor [1]. Composite objects are also often provided, e.g., by adding balls, pipes or pieces of hard wood to a metal chain.…”
Section: Pig Enrichment In Global Practicementioning
confidence: 99%
See 2 more Smart Citations
“…These objects do not meet the needs of pigs (as defined above) and can pose a hazard as they are unsafe (e.g., ingestible metal parts in car tyres [35]). Many studies have confirmed that objects such as chains, plastic pipes and balls or car tyres should not be recommended for long-term use, as they are not effective enrichment (e.g., [87,88]), do not meet the criteria of effectiveness and can quickly lose their novelty factor [1]. Composite objects are also often provided, e.g., by adding balls, pipes or pieces of hard wood to a metal chain.…”
Section: Pig Enrichment In Global Practicementioning
confidence: 99%
“…It remains unclear whether pigs are deterred by soiled enrichment objects, an issue first raised by Blackshaw et al [91]. Recent studies confirm lower interaction with logs presented on the floor, versus a hanging log, possibly caused by soiling with faeces [87]. However, the study on this issue by [96] found that cleaning (plastic and rubber) objects did not affect the pigs’ interaction with them.…”
Section: Pig Enrichment In Global Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, the Model Code of Practice for the Welfare of Pigs recommends that tail docking be avoided wherever possible. Where tail biting is a problem, all areas of the environment, feeding and management should be investigated to identify contributing factors so that remedial action can be taken, e.g., provision of enrichment to reduce tail biting behaviour [6], and, where tail docking is practiced as a preventative measure, it should be conducted before seven days of age. The EU Council Directive 2008/120/EC prohibits routine tail docking, but the practice is still widely used in many member states.…”
Section: Introductionmentioning
confidence: 99%
“…psychosocial stress has been considered as an important risk factor driving gastrointestinal pathophysiology and disease susceptibility [3][4][5]. Recently, animal welfare has become of increasing concern to the swine industry as well as the general public [2], and the urgency for a reduction in the use of antibiotics in livestock has become evident with the development and spread of antimicrobial resistance [6][7][8]. Therefore, effective environmental enrichments in the farm, such as larger spaces, and the provision of rooting substrates, has been proposed as a potential strategy to improve pig welfare, as well as health.…”
mentioning
confidence: 99%